2005
DOI: 10.1038/sj.jea.7500441
|View full text |Cite
|
Sign up to set email alerts
|

Indirect sources of herbicide exposure for families on Ontario farms

Abstract: Although direct contact during mixing/loading, application or repair and clean-up is the major pathway by which individuals living on farms are exposed to herbicides, indirect sources such as contact with contaminated surfaces may also contribute. As part of a biomonitoring study to measure the nature and extent of exposure of farm families to herbicides, we attempted to identify potential indirect sources of exposure in a subset of 32 Ontario farms. Herbicide residues in drinking water samples as well as surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The houses from a subsample of participants in the Agricultural Health Study in Iowa had 2,4-D detected in all house dust samples, and the concentration was associated with spray applications (Curwin et al 2005). The Ontario Farm Family Health Study also reported residual contamination of several household surfaces with 2,4-D (Arbuckle et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…The houses from a subsample of participants in the Agricultural Health Study in Iowa had 2,4-D detected in all house dust samples, and the concentration was associated with spray applications (Curwin et al 2005). The Ontario Farm Family Health Study also reported residual contamination of several household surfaces with 2,4-D (Arbuckle et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Blue = women 17  μ g/L (RfD), women 340  μ g/L (ToxCast reverse dosimetry). Red = child 21  μ g/L (RfD), child 450  μ g/L (ToxCast reverse dosimetry) see for review [218, 221]. …”
Section: Figurementioning
confidence: 99%
“…Biomonitoring data for 2,4-dichlorophenoxyacetic acid (2,4-D) in urine samples are now available from a number of studies of both the general population (including preschool-age children) and farm applicators and their family members [Alexander BH, et al 2007; Arbuckle and Ritter 2005; Arbuckle et al 2002, 2004, 2006; Centers for Disease Control and Prevention (CDC) 2005; Morgan et al 2008]. Such data provide an integrated measure of absorbed dose from all pathways and routes of exposure.…”
mentioning
confidence: 99%